2013
DOI: 10.1002/pi.4627
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of three‐dimensional multi‐walled carbon nanotube–graphene nanofiller in enhancing the mechanical and thermal properties of high‐performance silicone rubber

Abstract: The homogeneous dispersion of nanofillers and filler–matrix interfacial interactions are important factors in the development of high‐performance polymer materials for various applications. In the present work, a simple solution‐mixing method was used to prepare multi‐walled carbon nanotube (MWCNT)–graphene (G) (3:1, 1:1, 1:3) hybrids followed by their characterization through wide‐angle X‐ray diffraction, transmission electron microscopy and thermogravimetric analyses. Subsequently, MWCNT–G (1:1) hybrid was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
87
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(91 citation statements)
references
References 87 publications
4
87
0
Order By: Relevance
“…As a consequence, co‐dispersion of both the MWCNT and CRGO components is not achieved in MWCNT–CRGO (1:2, 2:1). Similar observations have recently been reported earlier in the literature . Therefore, dispersion stability of MWCNT–CRGO (1:1) hybrid indicates that this hybrid can be used as filler in TPU matrix.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As a consequence, co‐dispersion of both the MWCNT and CRGO components is not achieved in MWCNT–CRGO (1:2, 2:1). Similar observations have recently been reported earlier in the literature . Therefore, dispersion stability of MWCNT–CRGO (1:1) hybrid indicates that this hybrid can be used as filler in TPU matrix.…”
Section: Resultssupporting
confidence: 90%
“…MWCNT shows a sharp peak at 2 θ = 26°corresponding to 002 plane. However, in hybrid the peak intensity of MWCNT becomes weak and the peak broadens compared to MWCNT due to hybrid interaction …”
Section: Resultsmentioning
confidence: 99%
“…A simple solution method was used by Pardhan, B. et al[243] to enhance the thermal and mechanical properties of high performance silicon rubber with MWCNT and graphene (G). They prepared the hybrids in different proportions i.e.…”
mentioning
confidence: 99%
“…Yang et al also demonstrated remarkable synergy between graphene platelets (MGPs) and multi walled carbon nano tubes (MWCNTs) in improving the mechanical and thermal conductivity of epoxy composites . This concept has been adopted by our research group for the preparation of a range of new generation 3D hybrid fillers such as MWCNT/MMT, MWCNT/LDH, MWCNT/graphene in the development of polymer nanocomposites of silicone rubber (SR) and thermoplastic polyurethane (TPU) . Dubois et al used polyethene coating on MWCNT in order to improve level of dispersion in EVA leading to substantial improvement in its mechanical properties and thermo‐oxidative stability .…”
Section: Introductionmentioning
confidence: 99%